Numerical Modeling and Experimental Characterization of Elastomeric Pads Bonded in a Conical Spring under Multiaxial Loads and Pre-Compression. (4th February 2019) - Lalo, Debora Francisco; Greco, Marcelo; Meroniuc, Matias
Abstract : Elastomeric components are widely used in the engineering field since their mechanical properties can vary according to a specific condition, enabling their applications under large deformations and multiaxial loading. In this context, the present study seeks to investigate the main challenges involved in the finite element hyperelasticity simulation of rubber-like material components under different cases of multiaxial loading and precompression. The complex geometry of a conical rubber spring was chosen to deal with several deformation modes; this component is in the suspension system placed between the frame and the axle for railway vehicles. The framework of this study provides the correlation between axial and radial stiffness under precompression obtained by experimental tests in prototypes and virtual modeling obtained through a curve fitting procedure. Since the material approaches incompressibility, different shape functions were adopted to describe the fields of pressure and displacements according to the finite element hybrid formulation. The material parameters were accurately adjusted through an optimization algorithm implemented in Python program language which calibrates the finite element model according to the prototype test data. However, as an initial guess, the proper constitutive model and its parameters were first defined based only on the uniaxial tensile test data, since this test is easy to perform and well understood. The validation of the simulation results in comparison with the experimental data demonstrated that care should be given when the same component is subjected to different multiaxial loading cases.